Interventions addressing men, masculinities and gender equality in sexual and reproductive health and rights: an evidence and gap map and systematic review of reviews. Issue 5 (11th September 2019) - Ruane-McAteer, Eimear; Amin, Avni; Hanratty, Jennifer; Lynn, Fiona; Corbijn van Willenswaard, Kyrsten; Reid, Esther; Khosla, Rajat; Lohan, Maria
Abstract : Objectives: Working with men/boys, in addition to women/girls, through gender-transformative programming that challenges gender inequalities is recognised as important for improving sexual and reproductive health and rights (SRHR) for all. The aim of this paper was to generate an interactive evidence and gap map (EGM) of the total review evidence on interventions engaging men/boys across the full range of WHO SRHR outcomes and report a systematic review of the quantity, quality and effect of gender-transformative interventions with men/boys to improve SRHR for all. Methods: For this EGM and systematic review, academic and non-academic databases (CINAHL, Medline, PsycINFO, Social Science Citation Index-expanded, Cochrane Library, Campbell Collaboration, Embase, Global Health Library and Scopus) were searched using terms related to SRHR, males/masculinities, systematic reviews and trials (January 2007–July 2018) with no language restrictions for review articles of SRHR interventions engaging men/boys. Data were extracted from included reviews, and AMSTAR2 was used to assess quality. Outcomes were based on WHO reproductive health strategy. Results: From the 3658 non-duplicate records screened, the total systematic reviews of interventions engaging men/boys in SRHR was mapped through an EGM (n=462 reviews) showing that such interventions were relatively evenly spread across low-income (24.5%), middle-income (37.8%) and high-income countries (37.8%). The proportion of reviews that included gender-transformative interventions engaging men/boys was low (8.4%, 39/462), the majority was in relation to violence against women/girls (n=18/39, 46.2%) and conducted in lower and middle-income countries (n=25/39, 64%). Reviews of gender-transformative interventions were generally low/critically low quality (n=34/39, 97.1%), and findings inconclusive (n=23/39, 59%), but 38.5% (n=15/39) found positive results. Conclusion: Research and programming must be strengthened in engagement of men/boys; it should be intentional in promoting a gender-transformative approach, explicit in the intervention logic models, with more robust experimental designs and measures, and supported with qualitative evaluations.